Molecular dynamics simulations of phase behaviour and structural studies of guanidinium triflate ionic liquid and its mixture with water and N-methyldiethanolamine for carbon dioxide removal / Naimah Haron - Naimah , Haron (2020)
Molecular dynamics (MDs) simulations with an all-atom force field have been carried out to understand the phase equilibrium behaviour of aqueous guanidinium triflate [gua][OTf] ionic liquid (IL) (binary system) at 440.15 K, as well as the phase equilibrium behaviour of N-methyl diethanolamine (MDEA) with aqueous [gua][OTf] IL (ternary system) at 298.15 K. This work further elaborated the understanding of absorption mechanism of carbon dioxide (CO2) into ternary system at 298.15 K. For binary system, the simulations measured changes in different physical properties such as density, structural, bonding properties (radial distribution function (RDF)), water clustering and hydrogen bonding) and dynamic property (diffusion coefficient (D)). It was observed that water molecules started to connect with one another and formed a large hydrogen bond network throughout the system with an increasing water molar fraction. While for the ternary system, it is shown that the molecular level is slightly affected by the presence of MDEA and [gua][OTf] molar fractions. For MDEA-water interactions in [gua][OTf] media, MDEA prefers to be surrounded by water molecules rather than by MDEA molecules even at high MDEA molar fraction. Meanwhile, for [gua][OTf]-water interaction in MDEA media, as [gua][OTf] molar fraction increases, more water molecules replace counterions in the coordination shell of both [gua] and [OTf] ions, thus weakening their interaction. On the other hand, for MDEA-[gua][OTf] interactions in water media, it is found that, as the molar fraction of [gua][OTf] increases, a sulfonate group from [OTf] ion appears to have a stronger association by making hydrogen bonding with MDEA molecules. For the absorption mechanism of CO2 into a ternary system, the continuous increase of CO2 concentration does not affect the structure of IL, but CO2 molecules are always captured by the cavity of [gua] ion. Based on the physical properties of the ternary system, these ternary solvents can potentially be further studied to remove CO2 using aqueous MDEA and IL at high pressure in the natural gas industry.